Optimization of Multi-Product Distribution with Modification of The Modified Exponential Approach Method - Dwi Pajriah; Meliana Pasaribu; Mariatul Kiftiah (Department of Mathematics, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2025)
In the distribution of several different products, there is a condition where product allocation is not appropriate or there is a multi-product transportation problem. As a result, it is necessary to analyze the appropriate product allocation with minimum shipping costs. In solving this problem, a multi- product transportation problem model and modification of the Modified Exponential Approach method are proposed to obtain an allocation for each product with minimum shipping costs. In the case of the distribution of sweet snack products and spicy/salty snacks at the MSME Giu Store. Delivery is carried out using delivery services (J&T Express, Surya Cargo) and private delivery. Therefore, this problem is a form of transshipment problem. This problem is transformed into a multi-product transportation problem and solved by modifying the Modified Exponential Approach method. The calculation results show that private delivery is inefficient. It is recommended that products be distributed by J&T Express with delivery to the Sambas, Sekadau, and Sintang areas. Surya Cargo delivers to the Sanggau, Mempawah, and Singkawang areas. With this allocation, a minimum distribution cost of Rp 1,378,398 is obtained.